2022
DOI: 10.1093/mnras/stac1643
|View full text |Cite
|
Sign up to set email alerts
|

Quantum study of the bending relaxation of H2O by collision with H

Abstract: Vibrationally excited levels of the H2O molecule are currently detected in various environments of the interstellar medium (ISM), and collisional data for H2O, including vibration with the main colliders of the ISM, are needed. The present study focuses on the bending relaxation of H2O by collision with H when taking bending–rotation coupling explicitly into account with the rigid-bender close-coupling (RB-CC) method. With this aim, a new four-dimensional potential energy surface including the H2O bending mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 36 publications
5
15
1
Order By: Relevance
“…They used a full dimensional PES [16] and studied the vibrational relaxation of the system using the CC method and tested the validity of the Rigid Rotor Approximation for n 2 ¼ 0; n 2 ¼ 1 levels. While this latter study demonstrated that full dimensional calculations are possible for this system, the coupling between bending and stretching is quite small in the n 2 ¼ 1 state making possible to carry out scattering calculations using the Rigid-Bender approximation [17] in order to compare our results with the experimental works available as was already done successfully for the collisions of H 2 O with He [18] and H. [19] The other important objective of the present work is to study the inelastic collision of Ar with D 2 O and to compare the two systems as the only study investigating these effects was done using a semi-classical approach. [12] To this aim two 4D PES for Ar-H 2 O and Ar-D 2 O, including an explicit dependence on the bending angle are developed.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…They used a full dimensional PES [16] and studied the vibrational relaxation of the system using the CC method and tested the validity of the Rigid Rotor Approximation for n 2 ¼ 0; n 2 ¼ 1 levels. While this latter study demonstrated that full dimensional calculations are possible for this system, the coupling between bending and stretching is quite small in the n 2 ¼ 1 state making possible to carry out scattering calculations using the Rigid-Bender approximation [17] in order to compare our results with the experimental works available as was already done successfully for the collisions of H 2 O with He [18] and H. [19] The other important objective of the present work is to study the inelastic collision of Ar with D 2 O and to compare the two systems as the only study investigating these effects was done using a semi-classical approach. [12] To this aim two 4D PES for Ar-H 2 O and Ar-D 2 O, including an explicit dependence on the bending angle are developed.…”
Section: Introductionmentioning
confidence: 88%
“…The Close Coupling calculations were carried out separately for each of the ortho‐ and para‐ forms of H 2 O/D 2 O using our new PES and the Newmat code, [17] following the same methodology than in our previous works [17–19] . We performed both rigid rotor (RAST‐CC) and rigid bender (RB‐CC) calculations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the low vibrational frequency of SiCSi (o = 202 cm À1 ) 13 suggests that the inclusion of a bending motion in the close coupling calculations can affect the rate coefficients, as in the case of C 3 + He. 19 The rigid bender close-coupling method [20][21][22] requires a PES with an explicit dependence of the bending angle. If both molecules, SiCSi and H 2 , are considered rigid rotors, the expansion of the surface in the appropriate angular basis is far from being a straightforward procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Fitting coefficients of eqn(22) for the classical and semiclassical second virial coefficients (in cm 3 mol À1 ) This journal is © the Owner Societies 2023Finally, the computed B 12 coefficients were fitted to…”
mentioning
confidence: 99%